IC-LEE Model: A Financial Inclusion Framework for Strengthening Coastal Tourism Economies Based on Local Wisdom - Okta Eka Putra; Elan Rusnendar; Fillah Maulana Akbar (Journal of Management Studies and Development, 2026)
This study aims to examine the influence of local wisdom, financial innovation ecosystem, and financial inclusion on the development of the creative economy and local economic empowerment in coastal tourism at Benan Island, Lingga Regency. The research employed a quantitative approach using a model development study design. Data were analyzed through Structural Equation Modeling (SEM) using SmartPLS 4, and questionnaires were distributed to creative business actors and local communities. The results indicate that all proposed hypotheses were supported, showing that local wisdom, financial innovation ecosystem, and financial inclusion significantly affect the creative economy and local economic empowerment, both directly and indirectly through the mediation of financial inclusion and creative economy. The Adjusted R² values confirm that the model adequately explains the variance of the constructs, while the high Goodness of Fit demonstrates strong model suitability. These findings highlight the critical role of integrating local cultural values with financial innovation and creative economy development as an effective strategy to enhance sustainable community economic empowerment. The study provides practical implications for government, academics, and business actors to optimize collaboration in supporting the growth of a creative economy grounded in local wisdom.